Wealth effects of convertible-bond and warrant-bond offerings: a meta-analysis - Abdul Rahim, Norhuda; Goodacre, Alan; Veld, Chris (Taylor & Francis, 2014)
The literature on wealth effects associated with the announcements of convertible-bond and warrant-bond offerings is reviewed. The findings of 35 event studies, which include 84 sub-samples and 6310 announcements, are analysed using meta-analysis. We find a mean cumulative abnormal return of−1.14% for convertibles compared with−0.02% for warrant bonds, the significant difference confirming a relative advantage for warrant bonds. Abnormal returns for hybrid securities issued in the USA are significantly more negative than those issued in other countries. In addition, issuing hybrid securities to refund debt does not seem to be favoured by investors. Finally, several factors identified as important by theory or in prior research are not significant within our cross-study models, suggesting that more evidence is needed to confirm whether they are robust.